APLIKASI INVENTORI BARANG MENGGUNAKAN JAVA DENGAN PHPMYADMIN - Ertie Nur Hartiwati (Cross-border, 2022)
Problems that are increasingly complex from time to time in the world of work make the way of thinking must be more advanced. In carrying out an inventory of goods, a tool or method is needed that can utilize existing information in order to support business processes or activities in an organization so that its performance is more effective and efficient. Even though the world of technology has developed rapidly, there are still many entrepreneurs who manage inventory manually and are not yet connected to an integrated application. This Inventory application is made using Java and aims to provide complete information for companies, starting from tracking purchases, availability of goods, and sales.